2010
DOI: 10.1097/aog.0b013e3181cb9955
|View full text |Cite
|
Sign up to set email alerts
|

Term Stillbirth Caused by Oral Fusobacterium nucleatum

Abstract: Background-Intrauterine infection is a recognized cause of adverse pregnancy outcome but the source of infection is often undetermined. We report a case of stillbirth caused by Fusobacterium nucleatum that originated in the mother's mouth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
230
0
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(251 citation statements)
references
References 8 publications
8
230
0
13
Order By: Relevance
“…These studies demonstrated that bacteria administered intravenously make their way to placental tissue, proliferate there, and then invade into amniotic fluid and fetal tissues, eventually resulting in fetal resorption and stillbirth (Han et al 2004;Liu et al 2007). Further evidence for the hematogenous route of dissemination from oral to uterine tissue has come from analysis of bacterial isolates from oral and amniotic fluid sources in the same individual (Han et al 2010). Another study developed primer sets capable of distinguishing between the five subspecies of F. nucleatum and performed PCR using these primer sets on DNA isolated from different body sites of 10 women with localized periodontal pockets who delivered preterm (Gonzales-Marin et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies demonstrated that bacteria administered intravenously make their way to placental tissue, proliferate there, and then invade into amniotic fluid and fetal tissues, eventually resulting in fetal resorption and stillbirth (Han et al 2004;Liu et al 2007). Further evidence for the hematogenous route of dissemination from oral to uterine tissue has come from analysis of bacterial isolates from oral and amniotic fluid sources in the same individual (Han et al 2010). Another study developed primer sets capable of distinguishing between the five subspecies of F. nucleatum and performed PCR using these primer sets on DNA isolated from different body sites of 10 women with localized periodontal pockets who delivered preterm (Gonzales-Marin et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A less appreciated site of F. nucleatum infection is the reproductive tract; the organism can cause both vaginal (Hillier et al 1993;Hitti et al 2001;Holst et al 1994) and intrauterine infections (Altshuler and Hyde 1985;Chaim and Mazor 1992;Digiulio et al 2010). In fact, F. nucleatum is one of the most frequently isolated organisms from amniotic fluid of pregnant women who experience preterm labor (Chaim and Mazor 1992;Hill 1998;Bearfield et al 2002;Hitti et al 2001), and has also been associated with spontaneous miscarriage and stillbirth (Altshuler and Hyde 1985;Chaim and Mazor 1992;Han et al 2010). Periodontal disease, which is thought to affect~40% of reproductive age women (Boggess 2008), has also been linked with increased risks of pregnancy complications such as preterm birth and low birth weight (Offenbacher et al 1996;Dasanayake 1998;Pitiphat et al 2008;Guimaraes et al 2010;Saddki et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A case report of a stillbirth caused by F. nucleatum from the mother's mouth highlights the fact that an oral periodontal pathogen can, by hematologic pathway, colonize placenta and provoke fetal complications [20].…”
Section: Association Of Periodontal Health To Complications During Prmentioning
confidence: 99%
“…Hill demonstrated that Fusobacterium nucleatum can be isolated from amniotic fluid cultures of women with preterm labour and intact membranes suggesting the transient bacteraemia had originated from the mouth via haematogenous spread and infection of the amniotic fluid through the placenta [28]. More recently, Han and colleagues have reported a term stillbirth case by association was caused by Fusobacterium nucleatum, she had previously demonstrated that Fusobacterium nucleatum induced premature and term stillbirths in pregnant mice [29,30].…”
Section: Discussionmentioning
confidence: 99%